Aquaporin-4 in glioblastoma: a nexus of glymphatic dysfunction, edema, immune evasion, and treatment resistance - Castañeyra-Ruiz, Leandro; González-Marrero, Ibrahim; García-Abad, Luis H.; Gonzalez-Arnay, Emilio; Camacho, Marcial; Carmona-Calero, Emilia Ma; Lee, Seunghyun; Tran, Celine Thao-Quyen; Hanak, Brian W.; Muhonen, Michael; Castañeyra-Perdomo, Agustín (Frontiers in Cellular Neuroscience, 2025)
Glioblastoma (GBM) progression is linked to aquaporin-4 (AQP4), whose functions extend beyond water transport to influence perivascular architecture, immune modulation, edema, and treatment response. In the healthy brain, AQP4 is highly polarized at astrocytic endfeet, supporting perivascular fluid exchange and glymphatic clearance. In GBM, AQP4 is frequently upregulated and mislocalized, correlating with blood–brain barrier (BBB) disruption, impaired directional fluid movement, and peritumoral edema. Peritumoral astrocytic mislocalization of AQP4, together with tumor mass effect, compromises glymphatic function by distorting perivascular spaces and compressing cerebrospinal fluid (CSF)-Interstitial fluid (ISF) exchange zones. We review evidence that AQP4 isoforms (M1 vs. M23) differentially shape motility and membrane organization, and we outline how AQP4-linked signaling axes (e.g., indoleamine 2,3-dioxygenase 1 (IDO1)/tryptophan 2,3-dioxygenase (TDO)-kynurenine–aryl hydrocarbon receptor (AhR) can bias pro-invasive states and immunosuppressive niches enriched with M2-like macrophages). We integrate a four-zone perivascular framework to localize where GBM most perturbs periarterial and perivenous pathways, as well as meningeal lymphatic outflow. Finally, we discuss therapeutic directions spanning AQP4 modulation, isoform balance, and BBB-bypassing delivery strategies. Overall, AQP4 emerges as a mechanistic hub connecting BBB instability, glymphatic impairment, edema, immune evasion, and invasion in GBM.